Influence of Cold Atmospheric Plasma on Acinetobacter baumannii - Atta et al. (Baghdad Science Journal, 2019)
baumannii is an aerobic gram negative coccobacilli, it is considered multidrug resistance pathogen (MDR) and causes several infections that are difficult to treat. This study is aims to employ physical methods in sterilization and inactivation of A. baumannii, as an alternative way to reduce the using of drugs and antibiotics.